Knowledge management a practical guide for librarians - Bartlett, Jennifer A. (Practical guides for librarians ;, 2021)
"Knowledge Management: A Practical Guide for Librarians will help information professionals recognize, organize, communicate, and leverage both the tacit and explicit knowledge already in the organization for the benefit of themselves and their users"--